Histological Analysis and 3D Reconstruction of Winter Cereal Crowns Recovering from Freezing: A Unique Response in Oat (Avena sativa L.) - Livingston, David P. (Public Library of Science, 2013)
The crown is the below ground portion of the stem of a grass which contains meristematic cells that give rise to new shoots and roots following winter. To better understand mechanisms of survival from freezing, a histological analysis was performed on rye, wheat, barley and oat plants that had been frozen, thawed and allowed to resume growth under controlled conditions. Extensive tissue disruption and abnormal cell structure was noticed in the center of the crown of all 4 species with relatively normal cells on the outside edge of the crown. A unique visual response was found in oat in the shape of a ring of cells that stained red with Safranin. A tetrazolium analysis indicated that tissues immediately inside this ring were dead and those outside were alive. Fluorescence microscopy revealed that the barrier fluoresced with excitation between 405 and 445 nm. Three dimensional reconstruction of a cross sectional series of images indicated that the red staining cells took on a somewhat spherical shape with regions of no staining where roots entered the crown. Characterizing changes in plants recovering from freezing will help determine the genetic basis for mechanisms involved in this important aspect of winter hardiness.